AUGMENTED REALITY BASED VISUAL ATTENTION AND WORKING MEMORY ANALYSIS FOR CHILDREN USING COMPUTER VISION - A F M Saifuddin Saif; Zainal Rasyid Mahayuddin; Adil Mahmud Choudhury (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The mental learning arrangement of children and the impact of visual attention make computer vision researchers extremely inquisitive. Understanding child psychology in the early stage is one of the significant factors for their smooth mental growth which includes thinking patterns, learning styles, and psychological development. Visual inclining is one of the primary drivers of mental advancement in a child where the visual system is constrained by the subject’s eye. In this context, the idea of visual attention in children could uncover new learning patterns by means of the visual framework which is addressed by this research. Previous researchers attempted to discover various aspects in this context such as kid improvement, conduct acknowledgment, and field of intrigue where they did not use computer vision and augmented reality technology adequately. This research presents a rigorous investigation to learn about children’s psychological development through assigning interactive tasks to children. For this, this research developed a computer vision-based augmented reality system that gets a grouping of videos and identifies data from participating individuals. In this context, this research audited the coordination of eye, head, and hand developments amid the execution of a block copying assignment. Overall experimental investigation performed by this research presents a significant pattern to understand children’s phycology. The impacts of the proposed investigation using computer vision-based augmented reality will contribute significantly to design improved education materials for children from an early stage.